Bracken Fern Control in Pastures - Jason Ferrell; Brent Sellers; T. Wilson (EDIS)
Bracken fern is a poisonous plant common along tree lines, in forest openings, and around building borders. Animals will consume it when adequate forage is not available. Learn more in this 2-page fact sheet written by J. Ferrell, B. Sellers, and T. Wilson, and published by the UF Department of Agronomy, December 2011.